The Indian Tribal Art Market - Farzaneh Maleki Dizaji (Journal of Social and Development Sciences, 2017)
Abstract: In the study of art market of Indian tribal, creativeeconomy, cultural economy effect on consumer behavior, governmentprotection, changes of cultural believes and religion by tribal for increasing market, art economic etc. has been considered. In Indian tribal art economics, creative imagination coming from their culture, believes, religions etc. So it becomes more sensitive and restricted. The Field work was conducted in Bhopal (IGRMS), Madhya Pradesh, India. Data collection was performed by qualitative informal depth interview and quantitative data by questionnaire. Tools and technique were including photography, observation; case study (Bhil and Rathwa communities) Research duration was fromMay2015 to March 2016. Consumers of Indian tribal art divided to four categories: foreigners, NRI, artist and very rare common people. The government protection of Tribal art is based on Article 342. The protection is governed by the Ministry of Culture and Ministry of Tribal affairs, Government of India. And also by organizations like IGRMS, TRIFED, TRTI, Lalit Kala Academy etc. Protection of arts in India is performed under section 22 of the copy right Act 1957, intellectual property right and also scheme of “Market Development of Tribal Products/ Produce. In conclusion art marketing doesn’t have a particular formula for all type of art because they have different target audience.Keywords: Art Market, Creative Economy, Cultural Economy, Indian Tribal Art, Indira Gandhi Rashtriya Manav Sangrahalaya (IGRMS)